HUBUNGAN ANTARA PERSEPSI GAYA KEPEMIMPINAN ATASAN DENGAN KEPUASAN KERJA PEGAWAI PUSKESMAS MEKAR BARU - Uzlah, Siti Maria (Jurnal Psikologi, 2011)
AbstrakThe main purpose of this study was to examine the relationship between perceptions of supervisor leadership style and job satisfaction on employee health center New Blooms. This study uses sampling techniques saturated. The subject of this research are 32 employees. Data was collected using two questionnaires: transformational leadership style, transformational leadership style, and job satisfaction questionnaire. Data were analyzed using Pearson Product Moment correlation. The results are: (1) a positive and significant relationship between perceptions of supervisor leadership style and job satisfaction, (2) a positive and significant relationship between perceptions of transformational and transactional leadership style and job satisfaction.Â Kata Kunci: persepsi, gaya kepemimpinan, kepuasan kerja